Atherosclerotic vessel damage in systemic lupus erythematosus and antiphospholipid syndrome in men - A. I. Iljina; N G Klyukvina; E N Alexandrova; T V Popkova; A. A. Novikov; E S Mach; O V Bulgakova; E L Nasonov (Научно-практическая ревматология)
Objective. To study prevalence of clinical and subclinical atherosclerosis signs in men with systemic lupus erythematosus (SLE) and antiphospholipid syndrome, to assess relationship between atherosclerotic vessel damage, risk factors, CRP and anti-cardiolipin antibodies (АСА) Material and methods. 62 pts were included. Mean age was 35,7+11,6 years, mean disease duration - 129,3± 102 months. Traditional and related to the disease risk factors were analyzed. To reveal atherosclerotic vessel damage carotid sonographic examination was performed. Serum CRP concentration was evaluated by high sensitivity nephelometric immunoassay. IgG and IgM АСА were assessed by solid-phase immuno-enzyme assay. Results. Sonographic signs of carotid damage was revealed in 58% of pts, clinical signs of atherosclerosis - in 42%. Pts were divided into two groups according to intima-media complex thickness (IMCT). Group I included 36 pts with atherosclerotic vessel damage signs (IMCT?0,9 mm). Group 2-26 pts with IMCT<0,9 mm. Mean age at the examination, age of disease onset, disease duration, smoking frequency damage index in group I pts were higher than in group 2 pts. Mean CRP concentration in atherosclerosis group was significantly higher than in group 2 (p=0,007). 19 pts had APS signs. 43 pts did not. CRP level significantly correlated with IMCT in SLE pts with and without APS (p<0,05). Pts with atherosclerosis had higher IgG АСА level though the differences were not statistically significant. Conclusion. Men with SLE with or without APS have high risk of atherosclerosis development. CRP elevation is associated with IMCT increase.